Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Matematika Realistik - Misrina, Misrina (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This learning aims to improve students' mathematics learning outcomes through a realistic learning model in class IV SD Negeri 7 Samalanga, which has a total of 21 students. This research is a classroom action research conducted in 2 cycles. The results of the research cycle 1 showed that the activities and student learning outcomes of student learning outcomes were still low. Student learning activities based on the observations of 2 observers obtained a value of 79% and were still in the sufficient category. The acquisition value of the final test of cycle I, it is known that only 5 students achieved class completeness with a grade passing percentage of 23.80%. Therefore, the researcher continued the research into cycle II. In cycle II there was an increase in both the activity and student learning outcomes. Acquisition of scores on student learning activities 93.33% is in the very good category, as well as student learning outcomes tests increased to 85.71%. This means that cycle II has been successfully carried out both in terms of process and student learning outcomes. So it can be concluded that the results of a realistic mathematics learning model can increase the activity and results of students' mathematics learning.